The Bunch Grape - P.C. Andersen (EDIS, 2017)
This document provides an overview of bunch grape cultivation in Florida, focusing on the challenges posed by Pierce's disease and the development of resistant varieties. It details the propagation, planting, and maintenance practices necessary for successful grape production, including grafting techniques, trellising, pruning, fertilization, and pest control. The document emphasizes the importance of disease management and proper irrigation to ensure healthy grapevines and optimal yields. It also highlights the specific grape varieties best suited for Florida's climate and soil conditions. Publication date, August 2001.